2019
DOI: 10.1002/ange.201910588
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Area Aminated‐Graphdiyne Thin Films for Direct Methanol Fuel Cells

Abstract: At wo-dimensional (2D) carbon nanofilm with uniform artificial nanopores is an ideal material to ultimately suppress the fuel permeation in the proton exchange membrane fuel cells.G raphdiyne has great mechanical strength, high dimensional stability,a nd controllable nanopores,a nd has good prospects to playt his crucial role.I ti sf ound that graphdiyne nanofilm with amino groups and natural nanopores can be easily prepared with high integrity.The aminated graphdiyne has good compatibility with the Nafion mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…have been synthesized [58, 59] . Moreover, many sorts of heteroatoms or groups doped GDY have been successfully developed [33, 60, 61] . Nevertheless, so far, almost all of the GDY‐based ACs have been prepared on few‐layered nanosheets [60] .…”
Section: Discussionmentioning
confidence: 99%
“…have been synthesized [58, 59] . Moreover, many sorts of heteroatoms or groups doped GDY have been successfully developed [33, 60, 61] . Nevertheless, so far, almost all of the GDY‐based ACs have been prepared on few‐layered nanosheets [60] .…”
Section: Discussionmentioning
confidence: 99%
“…have been synthesized [58, 59] . Moreover, many sorts of heteroatoms or groups doped GDY have been successfully developed [33, 60, 61] . Nevertheless, so far, almost all of the GDY‐based ACs have been prepared on few‐layered nanosheets [60] .…”
Section: Discussionmentioning
confidence: 99%
“…Using such a molecular engineering strategy, different heteroatom elements can be introduced into GDY materials with precise control over the substituted position, heteroatom-doping configuration, heteroatom content, and the corresponding nanopore sizes. In the meantime, some previous studies have shown that the heteroatom-doped GDYs have great potential applications, as well as GDYs, in many fields. For instance, several qualitative and quantitative nitrogen-, halogen- (F, Cl), and B-doped GDYs have been synthesized and already shown high reversible capacity and extremely stable cycle performance in Li-ion storage and excellent catalyst activity in NADH regeneration . However, most of the heteroatom-doped GDY materials so far reported have been synthesized by postmodifying the preformed GDY materials, which was usually the so-called “top-down” strategy .…”
Section: Introductionmentioning
confidence: 99%